Capability of leaf water content and its threshold values in reflection of soil–plant water status in maize during prolonged drought - Huailin Zhou (Elsevier, 2021)
Leaves play an important role in plant growth and development through photosynthesis and transpiration. Many studies have explored the effects of short-term drought stress on leaf water status; however, few studies have focused on the leaf water content capacity as an indicator of soil–plant water status during prolonged droughts. The results of a field experiment with various irrigation regimes that was conducted during two consecutive maize growing seasons from 2013 to 2014, indicated that the water content of the first fully expanded leaf (LWCtop1) was representative of the soil–plant water status with the development of drought. LWCtop1 was closely linked to the water condition of other leaves and different plant parts in response to progressive water stress. LWCtop1 shared a quadratic relationship with the photosynthetic rate (Pn), and Pn peaked when LWCtop1 approached 84.11% and decreased to zero when LWCtop1 dropped to 68.26%. Moreover, three stages (slow-fast-slow) were observed as leaf water content responded to soil drying, and two important threshold values (minimum: 70.86 ± 0.80%, maximum: 84.58 ± 1.10%) of the leaf water content were determined. The results of this study may provide a physiological and ecological basis for the identification and monitoring of crop drought.